2009
DOI: 10.1016/j.neuroimage.2008.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Event-related brain potentials during the monitoring of speech errors

Abstract: a b s t r a c t a r t i c l e i n f oWhen we perceive speech, our goal is to extract the meaning of the verbal message which includes semantic processing. However, how deeply do we process speech in different situations? In two experiments, native Dutch participants heard spoken sentences describing simultaneously presented pictures. Sentences either correctly described the pictures or contained an anomalous final word (i.e. a semantically or phonologically incongruent word). In the first experiment, spoken se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 75 publications
(115 reference statements)
2
23
0
Order By: Relevance
“…This is in accordance with the findings reported in Schiller et al (2009). Similar PMNs for color and determiner error suggests that the correct word forms have been predicted for both error types.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is in accordance with the findings reported in Schiller et al (2009). Similar PMNs for color and determiner error suggests that the correct word forms have been predicted for both error types.…”
Section: Discussionsupporting
confidence: 92%
“…When spoken sentences were task relevant, the authors found phonological mismatch negativity (PMN) effects for both semantic and phonologically incongruent conditions compared to the correct condition. This negativity was followed by an N400 that was larger for semantic compared to phonological errors (Schiller et al, 2009). In the present study, we expect to obtain different ERPs for two types of errors.…”
Section: Introductionmentioning
confidence: 49%
See 3 more Smart Citations